Hypersensitivity to DNA damage in antephase as a safeguard for genome stability - Femke M. Feringa; Lenno Krenning; André Koch; Jeroen van den Berg; Bram van den Broek; Kees Jalink; René H. Medema (Nature Communications, 2016)
The DNA damage response induces a reversible arrest at different cell cycle stages. Here the authors find that loss of the APC/C inhibitor Emi1 in antephase (late G2) results in hypersensitivity to DNA damage and cell cycle exit at DNA damage levels that induce a reversible arrest in early G2.